Uma investigação acerca da ação numa perspectiva filosófica em Kant e Hegel. - Rio Tinto, Ítalo Rafael França (2022)
Considering the emerging relevance of the study concerning the action in Philosophy, a reflection of the advent of a discipline by the name Philosophy of Action, this work intents to investigate the action in the thoughts of Kant and Hegel, two important figures of Modern Idealism and the History of Philosophy as a whole. Therefore, the purpose is to analyze the 3rd Antinomy of Kant‟s Critique of Pure Reason and Hegel‟s Philosophy of Right in search of answers that points to the constitution and development of action, as well as, its practical relation with morality. All of that aimed at the defense that there is a Philosophy of Action in both Kant and Hegel. To this end, an analysis of the texts is carried out with the aim of reconstructing the thoughts of the mentioned authors and structuring an argument that supports the proposed objectives. Thus, it can be observed that despite the time in which they lived and the fact that it wasn‟t the authors‟ main objectives, it‟s possible to argue that exists a Philosophy of Action based on the vocabulary and conceptual structures of Kant and Hegel, which allows to conclude that both authors‟ philosophy, in a way, helped pave the way to the accomplishment of what we know today as Philosophy of Action. Also, it shows the importance of teaching philosophers like them nowadays.